The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2009
DOI: 10.1002/app.29952
|View full text |Cite
|
Sign up to set email alerts
|

Linear and branched polyoxide‐based copolymers: Methods to determine the CMC

Abstract: Evaluation of the physical-chemical properties of aqueous solutions of nonionic surfactants based on polyoxides can be performed by different methods. Depending on the technique used, there can be a significant variation in the critical micelle concentration (CMC) found. This is related to the sensitivity of the technique regarding the unimers and micelles present in the solution as well as the structure of the surfactant evaluated. In this work, the CMC values of aqueous solutions of linear and branched pol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2010
2010
2012
2012

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 17 publications
1
15
0
Order By: Relevance
“…The linear (L) and branched (B) PEO-PPO block copolymers used here were employed in a previous work 28 as demulsifiers, and it was observed that the branched copolymer was more efficient in breaking the synthetic water-in-oil emulsions tested. This efficiency was associated with: (i) their branched structure, where the EO and PO groups are more distributed in the chains, thus facilitating their dispersion between the phases of the W/O emulsion, and (ii) their average molar mass, since too long chains cannot diffuse through the oil phase because they form agglomerates and too short polymer chains diffuse too slowly, so requiring a molar mass near to an optimal value.…”
Section: Tests In the Presence Of The Demulsifier Additivesmentioning
confidence: 99%
“…The linear (L) and branched (B) PEO-PPO block copolymers used here were employed in a previous work 28 as demulsifiers, and it was observed that the branched copolymer was more efficient in breaking the synthetic water-in-oil emulsions tested. This efficiency was associated with: (i) their branched structure, where the EO and PO groups are more distributed in the chains, thus facilitating their dispersion between the phases of the W/O emulsion, and (ii) their average molar mass, since too long chains cannot diffuse through the oil phase because they form agglomerates and too short polymer chains diffuse too slowly, so requiring a molar mass near to an optimal value.…”
Section: Tests In the Presence Of The Demulsifier Additivesmentioning
confidence: 99%
“…42 To study the micellar behaviors of the heterograft copolymers herein with different compositions of PCL and PEG, the fluorescence technique has been employed and pyrene was used as a probe. As reported by Wilhelm et al, 47,48 pyrene molecules will transfer into hydrophobic microdomains with a concurrent change in the molecule's photophysical properties. In the excitation spectra, a sharp rise in the intensity ratio of the peaks at 338 and 333 nm of pyrene indicates the onset of micellization (CMC) for the amphiphilic copolymers.…”
Section: Micellization Of Heterograft Copolymersmentioning
confidence: 83%
“…Fluorescence excitation spectra were recorded on a HITACHI F-4500 fluorescence spectrometer at 390 nm emission wavelength and 2.5 nm slit width. Sample solutions for fluorescence investigation were obtained according to the literature, 47,48 and the concentration of the aqueous solutions ranged from 1.0 Â 10 À7 to 0.5 mg/mL. The pyrene concentration in the micellar solution was 6.0 Â 10 À7 mol/L.…”
Section: Preparation Of Micellesmentioning
confidence: 99%
“…As mentioned already, the PEO-PPO block copolymers and silicon polyethers grafted with PEO and PPO chains have a peculiar behavior when dissolved in water, because these solutions cloud when submitted to temperature variations, according to their affinities and interactions with the water molecules (Mansur et al, 2007;Silva et al, 2009).…”
Section: Solubility Tests Of the Additivesmentioning
confidence: 96%